PEKERJA SOSIAL MEDIS DALAM MENINGKATKAN KUALITAS KESEHATAN PASIEN: PERAN, TANTANGAN, DAN IMPLIKASI KEBIJAKAN DALAM SISTEM PELAYANAN KESEHATAN - Chriestine Lucia Mamuaya; Heru Dwi Herbowo; Yudi Harianto Cipta Utama; Fairuz Najla Athira; Zulfa Nabila Assegaf (Universitas Wijaya Kusuma Surabaya, 2026)
The complexity of the modern healthcare system demands an approach that not only focuses on the medical aspect but also pays attention to the social and psychological dimensions of patients. In this context, Medical Social Workers (MSW) play an important role as a liaison between patients and the health system to improve quality of life, especially for patients with chronic diseases. This study aims to analyze the role of MSW in improving the quality of life of patients through psychosocial support, facilitation of access to health services, and strengthening patients' capacity in managing their health conditions. The method used is a qualitative approach with literature study and conceptual analysis. The results of the study showed that MSW plays a significant role in helping patients overcome social barriers, reduce stress and anxiety, and increase participation in daily activities. MSW also contributes to promotive and preventive efforts through education and health promotion in the community. The existence of MSW is a strategic element in holistic health services. The integration of medical and social aspects through the role of MSW has been proven to support improving the quality of life of patients and strengthening the effectiveness of the overall health system. Policy implications from this study emphasize the importance of clear regulations, improved professional competence, and strengthened budget allocation for MSW professional development in Indonesia.